GRAIN YIELD OF MAIZE INOCULATED WITH DIAZOTROPHIC BACTERIA WITH THE APPLICATIONOF NITROGEN FERTILIZER - Alves, Gabriela Cavalcanti (2020)
Increasing the crop yield of maize planted in the climate and soil conditions of the northeast region of Brazil can be accomplished with the use of biological inputs coupled with the application of lower doses of nitrogen (N) fertilizer. The objective of this work was to evaluate the yield of maize inoculated with two diazotrophic bacterial species under different N rates, during three consecutive years in an Inseptisol of Sergipe state, Brazil. The two bacterial species used were Azospirillum brasilense BR11005 (Sp245) and Herbaspirillum seropedicae BR11147 (ZAE94). N was applied in the form of urea at 0, 100, 200, and 300 kg ha-1. Under field conditions and depending on the year, the crop yield was limited by the rainfall regime. The inoculation associated with the 100 kg ha-1 N treatment with BR11147 and BR11005, increased productivity by 1,230 kg ha-1 and 614 hg ha-1, respectively. This corresponded to a 37% and 19% productivity increase, respectively, compared to the productivity of the uninoculated control. At zero N, inoculation increased grain yield of maize plants inoculated with BR11147 by 18%. Additionally, the N content of the index leaf inoculated with BR11005 increased by 10% over that of the uninoculated control.